The Influence of Work Motivation on Employee Performance with Emotional Intelligence as A Mediating Variable in Insurance Companies in Pontianak City - Budiono, Martha; Siboro, Vika Oktaviani; Destriana, Odila Ivani (Universitas Syiah Kuala, 2025)
This study aims to analyse and determine the effect of work motivation on employee performance, with emotional intelligence as a mediating variable, in insurance companies located in Pontianak City. The sample used in this research consisted of 55 respondents who are employees working at insurance companies. Data were collected through questionnaires distributed via Google Forms, and the hypotheses in this study were tested using SEM-PLS (Structural Equation Modelling-Partial Least Squares). Statistical tests showed that the motivation variable has a significant positive effect on employee performance. In addition, t his study also proves that emotional intelligence can mediate the relationship between motivation and employee performance.